Macroeconomic Impact of Maternity (Parental) Leave Comparing the Czech Republic with Brazil - Kalkusová, Marie (2016)
This thesis aims to estimate the macroeconomic impact of maternity and parental/paternal leave in the Czech Republic and Brazil. In addition, the thesis stresses out the costs of Czech model application to Brazil and vice-versa. The first chapter brings a theoretical framework. It compares the analyzed policies in both countries and introduces the relevant terms. The second chapter estimates the costs of maternity and parental/paternal leave related to public expenditure and GDP for the years 2005-2014 and brings own simulation model for Czech model application to Brazil and vice-versa. The third chapter analyses the inefficiencies and suggest possible mitigation. The results show the costs of 0.71% of GDP and 1.66% of public expenditure in the Czech Republic and 0.50% GDP and 2.27% of public expenditure in Brazil in 2014. The Czech model applied in Brazil would be very costly and the opposite scenario would lead to the decrease of macroeconomic burden in the Czech Republic. The thesis also analyzes the influence of maternal and parental leave in other areas, such as labor market, where the current structure may penalize Czech women in long term. By this analysis, the thesis contributes to the current debate about the impact, the length and costs of maternity and parental leave.